1976
DOI: 10.1002/bit.260180708
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of some microbially induced flavor defects in milk and dairy foods

Abstract: SummaryThe "malty" flavor defect that commonly develops in raw milk produced in certain areas of North America and Europe has long been known to be due to the metabolic activity of Streptococcus lactis var. maltigenes. The identification of the aldehydes and alcohols responsible for this flavor defect and the mechanisms involved in their formation from amino acids are discussed.Pseudomonas jragi, a common psychrophilic recontaminant, is responsible for development of "fruity" flavors in processed dairy product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 30 publications
0
53
0
Order By: Relevance
“…In this two-step process, glycerides present in milk fat are first hydrolysed by lipases to liberate free fatty acids and glycerol, followed by the esterification of free fatty acids with an alcohol (in most cases, ethanol) to produce esters catalysed by esterases (Morgan, 1976;Kempler, 1983;Fox & Wallace, 1997;Fox, Guinee, Cogan, & McSweeney, 2000, Chapter 12).…”
Section: Mechanisms Of Ester Biosynthesis In Fermented Dairy Productsmentioning
confidence: 97%
“…In this two-step process, glycerides present in milk fat are first hydrolysed by lipases to liberate free fatty acids and glycerol, followed by the esterification of free fatty acids with an alcohol (in most cases, ethanol) to produce esters catalysed by esterases (Morgan, 1976;Kempler, 1983;Fox & Wallace, 1997;Fox, Guinee, Cogan, & McSweeney, 2000, Chapter 12).…”
Section: Mechanisms Of Ester Biosynthesis In Fermented Dairy Productsmentioning
confidence: 97%
“…Although previous work by Morgan,19 McIver and Reineccius 20 and Cheng and Reineccius 21 revealed that the addition of exogenous amino acids does not improve the yield of 2-methoxy-3-isopropylpyrazine in P. perolens, we examined the respective microbial growth of H. venusta and 2-methoxy-3-(1 0 -methylpropyl)pyrazine production by variation of the culture medium.…”
Section: -Methoxymentioning
confidence: 99%
“…According to Morgan (1976), lipids are involved in the formation of fruity aromas by P. fragi. If the formation of the aroma was proportional to the lipid concentration of the culture media, higher concentrations of odour-active metabolites should have been detected in skim milk (0.3% w of lipids/v).…”
Section: Discussionmentioning
confidence: 99%